MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK PADA MATERI DETERMINAN MATRIKS MELALUI MODEL PROBLEM BASED LEARNING - Siti Setiawati; Martin Bernard; M. Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to evaluate how students of class XI TKR 2 SMK Nurul Hidayah Pasundan develop their mathematical problem-solving skills using a problem-based learning technique on the topic of matrix determinants. This research is a classroom action research. The 2021–2022 school year's odd-numbered semester was employed for this study. There were 15 students of class XI TKR 2 who were used as research subjects. The following are the steps in this research: (1) Planning, (2) Action Implementation, (3) Observation and Evaluation, (4) Reflection. A learning outcome assessment used in this study measures students' ability to solve problems in relation to the determinants of the matrix., that is: (1) initial test, (2) first cycle test and second cycle test, (3) final test, and ( 4) observation sheets for researchers and students. The learning scenario had to be met by more than 80% of the activities performed in this study, and more than 80% of the individual students had to receive a score of at least 75. According to the study's findings, students in class XI TKR 2 at SMK Nurul Hidayah Pasundan can increase their capacity to solve mathematical problems by employing a problem-based learning approach when studying matrix determinants.